International relations : perspectives, controversies and readings - Shimko, Keith L. , 1962- (Wadsworth Cengage Learning, 2013)
INTERNATIONAL RELATIONS: PERSPECTIVES, CONTROVERSIES, AND READINGS, 4th Edition teaches readers to think critically about international politics. Taking an innovative approach, the text delivers brief, topical coverage with a debate ("point of view") framework; each topic has primary source readings. Increasingly relevant in our global community, and completely up to date, each chapter covers an important debate in the field. By looking at differing perspectives, the book encourages students to be able to use their conceptual and analytical tools to understand today's global issues, as well as be prepared to understand tomorrow's